Comparison of Low Back Pain in Working and Non-Working Pregnant Females - Kanwal Rizwan, Muhammad Yawar Azeem Khan, Syeda Rafia Mansoor, Muhammad Shahzad Qadree, Zeeshan Ahmed, Ibrar Muhammad Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pregnancy is the period during which a fetus develops inside the uterus or womb of a female. Low back pain is common during pregnancy, and it can have serious effects on physical, mental, emotional health during daily activities of living. Job routine commitments in working women may have impact on the level of low back pain during. Objective: To compare the low back pain in working and non-working pregnant females. Methodology: This was a descriptive cross-sectional study. The data was collected through validated Oswestry Disability Questionnaire and numeric pain rating scale from 121 pregnant females, 25 working and 96 non-working females, between the ages of 20 to 40 years with having low back pain working or non-working from Fatima Memorial Hospital, Lahore from October 2020 to March 2021 using non-probability convenience sampling. Statistical analysis was performed using SPSS 25.0 software. Result: The mean age of the study is 27.91. Independent t-test showed statistically non-significant difference between back pain of working (n=25, M=5.76, SD=0.413) and non-working (n=95, M=5.78, SD=.186) females, t(120)=.080, p=.936. the 95% confidence interval was -.0798 to 0.865. so, it failed to reject the null hypothesis. Also, there was no statistically significant difference between disability of working (n=25, M=12.68, SD=.8.112) and non-working (n=95, M=15.27, SD=8.350) females. t(120)=-1.390, p=.167. the 95% confidence interval was -6.282 to 1.100. so, it failed to reject the null hypothesis Conclusion: The findings of study concluded that both working and non-working females have a statistically non-significant, equal level of pain and disability due to low back pain during pregnancy. Keywords: Pregnancy, Low Back Pain, Working Women, Non-Working Women, Housewife, Female Job